509. Clinical Characteristics and Outcomes in Patients Infected with SARS-CoV-2 Treated with Remdesivir, Tocilizumab, and/or Dexamethasone at a Mid-Atlantic Hospital Consortium. (4th December 2021) - Darling, Nellie; Kent, Kristen R; Clark, Gavin; Geng, Xue; Kazanas, Marybeth; Kumar, Princy N; Timpone, Joseph G
Abstract: Background: Treatment strategies for COVID-19 have evolved based on clinical trials. We performed a retrospective analysis to determine treatment outcomes for Remdesivir (RDV), Tocilizumab (TOCI), and/or Dexamethasone (DEX) in a representative population from the Mid-Atlantic region. Methods: A retrospective chart review was performed for patients admitted to MedStar hospitals within the D.C./Baltimore corridor from 03/01/2020 to 12/31/2020, and diagnosed with COVID-19 using a NP SARS-CoV-2 RT PCR assay. The MedStar Pharmacy Database was utilized to stratify based on any combination of RDV, TOCI, DEX treatment. Our primary endpoints included O2 delivery device, length of stay (LOS), and mortality. Results: A total of 2488 patients were included. Overall, the average age of patients was 62yrs, 53% male, and the majority of patients were of Black (54%) or White (27%) race. The average length of stay was 11 days (SD = 12) with a mortality of 14%. Using univariate analyses, all combinations of RDV, TOCI, and DEX treatment regimens were evaluated. Patients who received DEX required the most ventilatory support on Day 1 (5%, p< 0.001) compared to all other groups. These same patients, however, did not go on to have higher ventilatory needs (17%, p< 0.001) compared to the group which ultimately required the most ventilatory support, TOCI plus DEX (94%, p< 0.001) at Day 28 of treatment. TOCI use alone was associated with a 4% to 63% (p< 0.001) increase in need for ventilatory support over the course of 28 days (Figure 1). The shortest LOS was seen in those treated with DEX alone (9.5 days, p< 0.001). Longer LOS outcomes were associated with all treatment groups which included TOCI use (19 to 22 days, p< 0.001, Figure 2). Mortality was similarly higher among all treatment groups which contained TOCI (30% to 62.5%, p< 0.001, Figure 3) when compared to those with RDV and/or DEX use alone (10% to 14%, p< 0.001). Barplot of Oxygen Delivery Device at Admission and within 28 Days among Treatments Figure 1. Largest increase in ventilatory support from Day 1 of treatment (left) to Day 28 of treatment (right) was seen among TOCI and DEX (0% to 93.8%), RDV and TOCI (0% to 72.2%) and TOCI alone (3.7% to 63.4%). Figure 2. LOS was higher among all treatments containing TOCI (p<0.001), with the highest being the combination group of RDV, TOCI, and DEX (22.4 days, p<0.001). Figure 3. Treatment regimens containing TOCI accounted for the highest mortality rates as seen in TOCI and DEX use (62.5%), RDV and TOCI (44.4%), and TOCI use alone (30.4%). Conclusion: Our study demonstrates that "real-world" clinical outcomes for patients with COVID-19 treated with Remdesivir, Tocilizumab, and Dexamethasone are consistent with what has been reported in clinical trials. The higher mortality associated with Tocilizumab treatment may reflect the use of this agent in critically ill patients with COVID-19. Disclosures: Princy N. Kumar, MD, AMGEN (Other Financial or Material Support, Honoraria)Eli Lilly (Grant/Research Support)Gilead (Grant/Research Support, Shareholder, Other Financial or Material Support, Honoraria)GSK (Grant/Research Support, Shareholder, Other Financial or Material Support, Honoraria)Merck & Co., Inc. (Grant/Research Support, Shareholder, Other Financial or Material Support, Honoraria)